SARS-CoV-2 infection in an insulin-dependent type I diabetic patient with subsequent ketoacidosis – Case Report - Santos, William Leal dos (2022)
Case report of a 28-year-old female patient, with medical history of type 1 diabetes mellitus, who was admitted to the emergency room at a regional hospital in her county due to a respiratory condition for 08 days presenting dyspnea, nausea, vomiting, abdominal pain and lowered level of consciousness. After initial evaluation was diagnosed with SARS-COV-2 acute viral infection through detectable RT-PCR test and concomitant diabetic ketoacidosis through clinical and arterial blood gas analysis. She was then transferred to a hospital in Manaus and admitted to an Intensive Care Unit bed, being discharged after 22 days of hospitalization with substantial improvement in her respiratory condition and resolution of the diabetic ketoacidosis. It was evident that there is an intimate correlation between SARS-CoV-2 infection and the occurrence of Diabetic Ketoacidosis in diabetic patients, in addition to the need for monitoring and ICU care for better outcomes.